UV cross-linking identifies four polypeptides that require the TATA box to bind to the Drosophila Hsp70 promoter. - Gilmour, D.S.; Dietz, T.J.; Elgin, S.C. (Molecular and Cellular Biology, 1990)
A protein fraction that requires the TATA sequence to bind to the hsp70 promoter has been partially purified from nuclear extracts of Drosophila embryos. This TATA factor produces a large DNase I footprint that extends from -44 to +35 on the promoter. A mutation that changes TATA to TATG interferes both with the binding of this complex and with the transcription of the hsp70 promoter in vitro, indicating that this interaction is important for transcriptional activity. Using a highly specific protein-DNA cross-linking assay, we have identified four polypeptides that require the TATA sequence to bind to the hsp70 promoter. Polypeptides of 26 and 42 kilodaltons are in intimate contact with the TATA sequence. Polypeptides of 150 and 60 kilodaltons interact within the region from +24 to +47 in a TATA-dependent manner. Both the extended footprint and the polypeptides identified by UV cross-linking indicate that the Drosophila TATA factor is a multicomponent complex.